Fleas (Insecta: Siphonaptera) with public health relevance in domestic pigs (Artiodactyla: Suidae) from Argentina - Sanchez, Juliana Patricia; Ezquiaga, María Cecilia; Ruiz, Melanie (Zootaxa, 2018)
The presence of fleas can have a great negative impact on the productivity and well-being of the animals, and can contribute towards propagation of causative pathogens of important diseases in animals and humans. Fleas and domestic pigs (Sus scrofa Linnaeus, 1758) are a known association. However, knowledge about fleas on pigs in Argentina is scarce. In this country, swine farming has become one of the main components of livestock production. This activity is primarily carried out by smallholder farmers, involving a potential risk to humans of acquiring pathogens. Our study was developed in Buenos Aires province, Argentina, in a region where there is strong swine livestock activity. We provide the first record for Argentina of Ctenocephalides felis felis (Bouché, 1835) and Pulex irritans Linnaeus, 1758 in domestic pigs, and the first data for the country of parasitological indexes of fleas in pigs. Ctenocephalides felis felis and P. irritans cause discomfort, nuisance, allergic reactions, and anaemia, and are known as vectors of several pathogens with importance for public health. The high prevalence and abundance of C. felis felis and P. irritans observed in pigs from Azul, Buenos Aires, are significant, and the absence of them in other studied localities could correspond to environmental characteristics. This paper expands the knowledge about the flea diversity associated with S. scrofa in Argentina and contributes to the knowledge of the ecology and biology of two cosmopolitan fleas and with public health relevance. This information is important for future epidemiological studies, as well as to establish prevention and control measures where appropriate.